The contralateral organization of the human nervous system as a quantum unfolded, holographic-like, artifactual representation of the underlying dynamics of a fundamentally two-dimensional universe - Zukauskis, Ronald L. (Frontiers in Systems Neuroscience, 2023)
A working hypothesis is put forward in this article that the contralateral organization of the human nervous system appears to function like a quantum unfolded holographic apparatus by appearing to invert and reverse quantum unfolded visual and non-visual spatial information. As such, the three-dimensional contralateral organization would be an artifactual representation of the underlying dynamics of a fundamentally two-dimensional universe. According to the holographic principle, nothing that is experienced as three-dimensional could have been processed in a three-dimensional brain. Everything we would experience at a two-dimensional level would appear as a three-dimensional holographic representation, including the architecture of our brains. Various research observations reported elsewhere are reviewed and interpreted here as they may be related in a process that is fundamental to the underlying two-dimensional dynamics of the contralateral organization. The classic holographic method and characteristics of image formation contained by a holograph are described as they relate to the working hypothesis. The double-slit experiment is described and its relevance to the working hypothesis.